2012
DOI: 10.1111/j.1365-2524.2012.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the economic recession on well-being and quality of life of older people

Abstract: The importance of economic well-being is recognised in the recent UK Government policy. Older people may be particularly vulnerable to economic fluctuations as they are reliant on fixed incomes and assets, which are reducing in value. Within the literature, little is understood about the impact of the current economic downturn on people's general quality of life and well-being and, in particular, there is little research on the financial experiences and capability of the older age group, a concern in light of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 26 publications
(32 reference statements)
0
42
0
6
Order By: Relevance
“…In addition, poverty rates for older adults in Mississippi are among the highest in the United States (Henry J. Kaiser Family Foundation, 2013). The role of finances also may have been exacerbated by the economic recession during which the survey was conducted (Fenge et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, poverty rates for older adults in Mississippi are among the highest in the United States (Henry J. Kaiser Family Foundation, 2013). The role of finances also may have been exacerbated by the economic recession during which the survey was conducted (Fenge et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of situations of economic hardship, financial threat, and lack of financial well-being also contributed to the appearance of negative psychological outcomes (Kim, Garman, & Sorhaindo, 2003;Marjanovic et al, 2013;Norvilitis et al, 2003). Well-being can be affected by work-related aspects (Fenge et al, 2012), such as job dissatisfaction and unemployment, two common situations in contexts of economic turmoil, which potentiate depressive symptoms. In turn, Prawitz et al (2006) observed that a perception of low financial well-being is responsible for an increase in distress levels.…”
mentioning
confidence: 99%
“…It is possible that unmeasured socioeconomic differences are responsible at least in part for the site differences. Detroit was suffering from a severe economic recession during the study time-frame, and depressed economic conditions have been shown to be associated with poorer well-being and quality of life in the elderly [19]. Our findings emphasize the limitations of single-site observational studies, which may not be generalizable to other settings.…”
Section: Discussionmentioning
confidence: 79%